Toward secure and accountable data transmission in Narrow Band Internet of Things based on blockchain - Hanshu Hong; Bing Hu; Zhixin Sun (International Journal of Distributed Sensor Networks, 2019)
The developments of Narrow Band Internet of Things have attracted much attention from both academia and industry nowadays. While Narrow Band Internet of Things is gradually designed for commercial applications, it also confronts with several security concerns such as identification and privacy. Blockchain technique is equipped with authentication, auditing, and accountability, and thus it can serve as a promising tool for providing secure data communication on the network. To enhance the security level and achieve reliable data authentication and accountability for Narrow Band Internet of Things system, in this article, we combine the merits of blockchain technique and propose a blockchain-based architecture for Narrow Band Internet of Things. The presented architecture consists of three layers which are sensing layer, transport layer, and transaction layer. We describe the interaction processes between each layer in detail and construct the algorithms which are used to conduct data authentication and blockchain generation. By evaluation, our scheme is demonstrated to obtain favorable performances in terms of privacy, authentication, accountability, and efficiency, which makes it an appropriate method to be applied for secure data communication in Narrow Band Internet of Things systems.